Comparative Biochemical Outcomes, Effectiveness and Tolerance of Densiron 68 and Oxane HD for the Management of Complicated Retinal Detachment - Chafik Keilani; Edouard Augstburger; Mathieu Robin; Amélie Beaugrand; Raphaëlle Ores; José-Alain Sahel; Sarah Ayello-Scheer (Türk Oftalmoloji Dergisi, 2019)

(untitled)
Objectives:To compare biochemical outcomes, effectiveness, and tolerance of two high-density silicone oils (HDSOs), silicone oil- RMN3 (Oxane® HD) and silicone oil-Densiron-68 (Densiron® 68), for the management of complicated retinal detachment (RD) associated with inferior proliferative vitreoretinopathy (PVR).Materials and Methods:This was a retrospective, single-centre, comparative case series of 23 patients treated between September 2014 and June 2016. The main inclusion criteria were RD with inferior PVR receiving Oxane® HD or Densiron® 68 following pars plana vitrectomy. The main outcome measures were anatomical success, rate of RD recurrence, and best-corrected visual acuity (BCVA) at 6 months. Secondary outcomes were short-term complications.Results:Twenty-three eyes were included: 16 eyes with Densiron® 68 tamponade and 7 eyes with Oxane® HD tamponade. Anatomical success under HDSO was significantly higher in the Densiron® 68 group (100%) than in the Oxane® HD group (42.8%) (p=0.0455). Recurrent RD was observed in 42.8% of eyes under Oxane® HD, but in none of the patients under Densiron® 68 (p=0.001). Six months after surgery, mean BVCA values (+/- standard deviation) with Densiron® 68 and Oxane® HD were 0.83±0.62 logMAR and 1.81±0.65 logMAR, respectively. BVCA was significantly better in the Densiron® 68 group (p=0.006). No significant differences were observed with regard to intraocular pressure, emulsification, or intraocular inflammation.Conclusion:Densiron® 68 appears to be more effective than Oxane® HD for the management of RD associated with PVR. A randomized, controlled, interventional study is needed to demonstrate this difference.